Determination of the Optimal Conditions of t he Bond of Nickel ( II) Ion Complex with Dimethyl glyoxime Reagent (Eurasian Research Bulletin, 2022)
This paper describes experimental methods for the separation of nickel ions from the adsorbent using dimethylglyoxime in the regeneration of adsorbents.A universal buffer solution with pH = 8.0 was used to study the dependence of the composition of buffer solutions on the main reaction Ni2+-Rreagent) components